Analysis of the impact of innovative digital technologies on regional socio-economic complexes - I. G. Ershova; P. V. Kovalenko; A. A. Sotnikov (Вестник Северо-Кавказского федерального университета)
Introduction. The article determines the importance of digital technologies in the development of the socio-economic complex of both the country as whole and individual regions. The essence and significance of the digital transformation process is determined. Particular attention is  paid  to  the  features  of  the  implementation  of  digital  technologies  at  the  level  of  business  structures.  The  level  of  use  of  advanced  production technologies  in  the  Central  Federal  District  is  analyzed,  and  state  measures  to  intensify  the  introduction  of  digital  technologies  into  the  socio-economic complex of the country and regions are also discussed. Goal. The conducted research specifies the possibilities of economic development in the context of digital transformation. The purpose of the study is to analyze the impact of digital technologies on regional socio-economic complexes. Materials and methods. To conduct the research, general scientific approaches and methods of analysis of research materials were used, as well as methods of statistical data processing, content analysis of strategic documents. Results and discussion. The authors highlight the levels of the digital economy.  The  main  advantages  of  the  digital  transformation  of  enterprises  are  considered.  The  technological  foundations  of  digitalization  are presented. The main indicators of the development of the digital economy in our country, the share of organizations that used the Internet, by constituent entity of the Russian Federation have been identified. The indicators of advanced production technologies used in the Central Federal District of the Russian Federation are presented by the constituent regions. Federal projects that are part of the national project “Digital Economy of the Russian Federation” have been systematized. Conclusion. The  introduction  of  digital  technologies  can  significantly  increase  the  efficiency  of  enterprises individually, as well as accelerate the development of regions as a whole. Yet, due to the uneven pace of development and implementation of these technologies  in  different  sectors  of  the  economy  and  individual  regions,  the  processes  of  digital  transformation  require  increased  attention  to  this aspect on the part of business community.